Music - Beresin, Eugene (Arts for health., 2022)
Music is an art form but also a social activity. It is a part of every human society, contributing to community, culture, and a sense of group identity. It is also fundamental to individual identity and personal well-being. In Music, Eugene Beresin traces the possible applications of musical expression for human health and happiness. At the heart of Music are powerful examples from the lives of real individuals, families, and populations. These stories cover a myriad of ages, instruments, situations, and purposes, to convey the universal power of music to help us all get more out of life. Offering practical ideas for integrating musical practice into a wide range of settings from the medical to the personal, Beresin provides a compelling evocation of the healing power of music. It is a must-read for practitioners, teachers, counsellors, and lovers of the art form.